Mine and Tablou 2 - Jehani, Hossein (World Is My Home Film Production, 2009)
Verzio FF Submission Sarwaz Sawz is an artist, in order to survive however, he had to work in a mine-field. Sarwat died two years after the first documentary "Mine & Tablou" was made. Hossein Jehani looks at the director's footage to find some pieces to put together for their anniversary. "Mine and Tablou 2" is the result of this initiative.